Prevalence of dental anomalies and genetic aberrations of nonsyndromic cleft-lip with or without cleft palate patients with hypodontia - Ghazali, Norliana (2022)
Non-syndromic cleft lip and or without cleft palate (NSCL/P) with dental anomalies are a common craniofacial abnormality in humans and animals. NSCL/P is reported to have a higher prevalence of dental anomalies compared to non-cleft individuals. This study aims to determine the prevalence of dental anomalies and to identify the genetic aberration among NSCL/P children using DNA microarray. A cross-sectional study was carried out at Hospital USM with a clinical oral examination followed by an orthopantomogram analysis among NSCL/P and non-cleft children between the ages of 7 to 13 years old. Saliva was collected from the subjects for genomic DNA extraction. Extracted genomic DNA from 61 NSCL/P and 20 non-cleft were subjected to the CytoScan 750K Array to identify genetic aberrations such as copy number variations (CNVs) and loss of heterozygosity (LOH). For CytoScan 750K Array, 250 ng of genomic DNA were digested with Nsp1, before being ligated to an adapter. Polymerase chain reaction (PCR) using a single pair of primers that recognised the adapter sequence was then performed. All four aliquots of PCR products were then combined and purified with magnetic beads followed by fragmentation with DNase 1 then subsequently end-labeled with biotin and hybridyzed into the CytoScan arrays. Next, the array was stained using GeneChips Fluidics Station 450 before scanning the arrays. The data was then analysed manually using the Chromosome Analysis Suite (ChAS) software to examine the genome. Statistical data analysis was performed using Mann-Whitney and Chi-Square test in the IBM SPSS software to confirm the significant results. The results showed that the prevalence (95% CI) of anomalies related to the number of teeth (67%:95% CI: 0.540,0.787) was higher than the morphology (8%;95% CI: 0.027, 0.181) in the NSCL/P children. The highest dental anomalies was hypodontia among NSCL/P and non-cleft children. Six significant CNVs were identified including gains (12q14.3, 15q26.3, 1p36.32, and 1p36.33) and losses (3p14.2 and 4q13.2) in the NSCL/P with hypodontia patients compared to the NSCL/P only. The genes encoded in these regions are LEMD3, IGF1R, TP73, SKI, FHIT, and UGT2β15. For LOH, the most recurrent regions were found at 1p33-1p32.3, 1q32.2-1q42.13, and 6p12.1-6p11.1 loci occurred in 13 (16%), 5 (6%) and 7 (9%) among NSCL/P and non-cleft with hypodontia children, respectively. Validation analysis revealed a significant copy number gain in TP73, SKI, IGF1R and LEMD3 and loss in FHIT and UGT2β15 in NSCL/P children with hypodontia (p < 0.005). Microsatellite markers analysis found a significant association between D1S197 (1p36.33-32.3) markers in NSCL/P with hypodontia. In conclusion, the present study has successfully determined the prevalence of dental anomalies and identified the genetic aberrations among NSCL/P. The current study shows a novel finding of copy number loss at 3p14.2 and 4q13.2 that includes FHIT and UGT2β15 which may contribute to the formation of NSCL/P with hypodontia. These results have an immerse prospect in the promising field of individualized preventive oral health care.